Borys Hrynchenko and Fedyr Matushevsky: epistolary dialogue - Yakobchuk, Nadija (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The complex of mutual correspondence between Borys Dmytrovych Hrinchenko and Fedir Pavlovich Matushevskyi - well-known public figures, representatives of the Ukrainian national movement of the beginning of the 20th century is analyzed in article. The content and source value of the epistolary dated 1902-1910 were studied. Texts of autographs of individual epistles are added to the article. The purpose of the research is to determine the thematic range, informational potential and source value of the correspondence for the study of the social and cultural life of Ukraine at the beginning of the 20th century, as well as to clarify the key stages of the life path of the respondents. Research methodology. The article is written on the basis of the principles of historicism, scientificity and systematicity. General historical and source research methods are applied: analytical, synthetic, chronological, heuristic, critical, archeographic and others. The scientific novelty is due to the lack of a comprehensive study of the correspondence of Borys Hrinchenko and Fedir Matushevsky, the need to involve it in scientific circulation. Conclusions. It has been established that the complex of correspondence between Borys Hrinchenko and Fedir Matushevsky has a small volume, but this does not diminish its value as a historical source. The thematic range and informational potential of the epistolary have been determined. Its significance for the study of the public life of Ukraine at the beginning of the 20th century, clarification of the facts of the respondents’ biographies, is revealed. The analysis of the correspondence provides an opportunity to investigate the publishing activities of the figures and the working conditions of the Ukrainian intelligentsia at the beginning of the 20th century. An important topic in the correspondence is the discussion of the events that took place in Kyiv region, Chernihiv region and Kharkiv region as a result of the 1905 revolution.